Analysis of The Rock Fracture on Uniaxial Compressive Strength Test - Dinoy, Edward; Tampaty, Yohanes Gilbert; Mabuat, Imelda Srilestari; Dwene, Joseph Alexon Sutiray (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2021)
The compressive strength test is one of the technical properties or compressive strength tests that are commonly used in rock mechanics to determine the collapse point or the elasticity of rock against maximum pressure. The rock collapse point is a measure of the strength of the rock itself when the rock is no longer able to maintain its elastic properties. The purpose of this test is to find out how long the rock maintains its strength or elasticity properties when pressure is applied, and to find out the difference between the strength of compact rock and rock that has fractures when pressure is applied. Rocks that have fractures will break more easily or quickly when pressure is applied compared to compact rocks. This analysis is carried out by comparing the rock strength of each sample, both those that have fractures and compact rocks. To find out these differences, laboratory testing was carried out. The test results show the value (compressive strength test 57.76 MPa), (elastic modulus 5250.000MPa), (Poisson ratio 0.05) and the average value of rock mechanical properties test (axial 0.91), (lateral-0.279), and (volumetric 0.252) . Based on the test results above, it shows that rocks that have fractures will break more easily when pressure is applied, compared to compact rocks that have a long time in the uniaxial compressive strength test.